The direct and moderating role of coping strategies on the relationship between financial anxiety, academic demands, and psychological well-being among undergraduate students: a PLS-SEM approach - Ridho Candra; Zadrian Ardi (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Psychological well-being among undergraduate students has emerged as a critical academic outcome shaped by multiple interacting stressors. This study examined the direct effects of coping strategies, financial anxiety, and academic demands on psychological well-being, as well as the moderating role of coping strategies in those relationships. A quantitative approach was applied in this study by utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method on a sample of undergraduate students. Results indicated that coping strategies positively and significantly predicted psychological well-being (β = 0.381; p < 0.05), while financial anxiety exerted a significant negative effect (β = -0.307; p < 0.05). Academic demands did not demonstrate a significant direct effect, likely because students’ subjective appraisals of academic load are modulated by internal regulatory factors such as self-efficacy and resilience. Moderation analysis revealed that coping strategies significantly attenuated the negative impact of financial anxiety on psychological well-being (β = 0.292; p < 0.05) indicating that higher coping capacity was associated with a weaker negative effect of financial anxiety whereas its moderating role in the academic demands relationship was not supported. These findings suggested that adaptive coping capacity represented a stronger determinant of student well-being than external academic pressure, and that financial anxiety constituted a distinct psychological burden warranting targeted institutional intervention.